Queering fat bodies, regulating teen desire in ABC Family's Huge. Issue 2 (2nd July 2016) - Kosier, Rebekah A.; Renfrow, Daniel G.
ABSTRACT: This essay examines the intersections of fatness, youth, and sexuality in ABC Family's Huge, a sitcom about teens at "fat camp." The series departs from common "fat kid" tropes of the past because it consciously presents fat teens as sexual subjects and some fat bodies as objects of desire. Public bodily displays and chosen names, however, mark Willamena and Alistair, campers who resist either the camp's ideology of weight loss or the gender binary upon which it is constructed, as queer. Moreover, Huge uses metaphors of (un)cleanliness and of the closet to simultaneously regulate these characters' fatness and queerness. Although Huge initially promises to destabilize the hegemony, the series ultimately falls short in its challenge to fat stigmatization and the gender/sexual regime.